The Effect of Profit Management on Companies Listed in BEI Food and Beverage Sub-Sector - Nadjib, Nadjib; Saputra, Hendra; Agustina, Roro Colia (International Journal of Social Service and Research, 2023)
This study aims to determine the effect of audit quality and audit committee on profit management in food and beverage sub-secretary companies listed on the IDX in 2015-2020. This study uses quantitative research with the aim of determining the degree of relationship and pattern / form of influence between audit quality variables and audit committees on the company's profit management of the object of research. The results of this study can be explained that the quality of the audit has no effect on profit management of -1,402 < 2,034. Meanwhile, the audit committee affects profit management in food and beverage subsector companies listed on the IDX in 2015-2020, where the audit committee variable is 3,593 > 2,034. The quality of the audit and the audit committee simultaneously affects profit management where in the simultaneous test (Test F) it is known that the value of the F table is 3.28 with a significant value of 5% (0.05). F count 7.378 > F table 3.28 then Ho is accepted which means the quality of the audit, the audit committee simultaneously has a significant effect on profit management with a significance level of 0.002 <0.05. Furthermore, in the coefficient of determination test, it is known that the value of the coefficient of determination (R-Square) is 0.267. This value can be interpreted as variables X1 and X2 able to affect Y by 26.7%, the remaining 73.3% is explained by variables or other factors.